2020
DOI: 10.1186/s12891-020-03462-4
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent idiopathic scoliosis: evaluating perioperative back pain through a simultaneous morphological and biomechanical approach

Abstract: Background Adolescent idiopathic scoliosis (AIS) has been associated with diminished postural stability and a greater prevalence of back pain. Currently, the literature is lacking information on the effect of spinal fusion on both postural stability and its association with back pain. Our objectives were to evaluate the postsurgical effect of spinal morphological changes on static standing balance and assess the influence of these alterations on reported pain throughout the perioperative period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Also, other studies have not found statistically significant correlations between sagittal alignment and back pain. [35][36][37] However, a greater spinal deformity with increased radiological parameters of coronal Cobb angle, torsion index, and right thoracic translation did correlate with the likelihood of developing back pain. 36,37 To summarize, even though AIS patients are mostly clinically balanced in the sagittal plane, sagittal spinopel vic alignment is altered, with global flattening and anterior overgrowth of the spine.…”
Section: Sagittal Alignment In Ismentioning
confidence: 90%
See 1 more Smart Citation
“…Also, other studies have not found statistically significant correlations between sagittal alignment and back pain. [35][36][37] However, a greater spinal deformity with increased radiological parameters of coronal Cobb angle, torsion index, and right thoracic translation did correlate with the likelihood of developing back pain. 36,37 To summarize, even though AIS patients are mostly clinically balanced in the sagittal plane, sagittal spinopel vic alignment is altered, with global flattening and anterior overgrowth of the spine.…”
Section: Sagittal Alignment In Ismentioning
confidence: 90%
“…[35][36][37] However, a greater spinal deformity with increased radiological parameters of coronal Cobb angle, torsion index, and right thoracic translation did correlate with the likelihood of developing back pain. 36,37 To summarize, even though AIS patients are mostly clinically balanced in the sagittal plane, sagittal spinopel vic alignment is altered, with global flattening and anterior overgrowth of the spine. The occurrence of back pain in AIS seems to correlate more with the deformity in the cor onal plane than the sagittal alignment.…”
Section: Sagittal Alignment In Ismentioning
confidence: 90%
“…Other residual deformities and their relationship to pain have been explored by various studies. In a study by St. Georges et al, 69 participants completed the SRS-30 questionnaire and a modified version of the Adolescent Pediatric Pain Tool (APPT) to characterize pain. Pain score showed statistically significant improvements at 6 weeks and 6 months.…”
Section: Fusion Surgerymentioning
confidence: 99%
“…Initially, spinal morphology measurement based on computed tomographies (CTs) was a guide for the selection of path and safe margin in screw placement 9–11 . Some researchers attempted to probe how the morphological parameters affected disease manifestations such as back pain and IVD lesion 12,13 . For surgeons, understanding the spinal deformity progression will be helpful for the following surgical formulation.…”
Section: Introductionmentioning
confidence: 99%